Reinforcement film

By using the base material layer A1 and the adhesive layer A2 in the reinforcement film, the light reflectivity change in its specific environment is controlled, and the problem of the reduction in detectability caused by the change in reflectivity of the reinforcement film under severe environment is solved, and the effect of maintaining high detectability after long-term storage is achieved.

CN114729241BActive Publication Date: 2025-03-04NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080081630.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-26
Filing Date
2020-07-27
Publication Date
2025-03-04
Estimated Expiration
2040-07-27

AI Technical Summary

Technical Problem

During long-term storage under harsh environments, the reflectivity of the enhanced film will decrease the detectability.

Method used

The reinforcing film including the base material layer A1 and the adhesive layer A2 was used. The light reflectivity change rate at 580 nm after one week of storage under 60°C and 90% RH was controlled to be less than 2.0%, so as to ensure that the detectability is not reduced.

Benefits of technology

It effectively suppresses the reflectivity change of the film for enhancement, ensuring that high detection performance can be maintained after long-term storage in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114729241B_ABST
    Figure CN114729241B_ABST
Patent Text Reader

Abstract

The present invention provides a reinforcing film, which is a reinforcing film that can be attached to an optical component or an electronic component. When the optical component or the electronic component is detected through the reinforcing film, the change in reflectivity is suppressed and the detectability is not reduced. In addition, provided is: an optical component with a reinforcing film or an electronic component with a reinforcing film having such a reinforcing film. Furthermore, provided is: a reinforcing film with a surface protective film having a surface protective film in such a reinforcing film, and a method for using such a reinforcing film with a surface protective film. The reinforcing film according to an embodiment of the present invention is a reinforcing film comprising a substrate layer A1 and an adhesive layer A2, and the light reflectivity change rate at 580nm after the reinforcing film is stored in an environment of 60°C and 90% RH for 1 week is less than 2.0%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reinforcing film. Background Art

[0002] In order to impart rigidity and impact resistance to optical components and electronic components such as organic EL panels, LCD panels, and touch panels, reinforcing films are sometimes laminated to exposed surfaces of the optical components and electronic components for reinforcement (Patent Document 1).

[0003] Furthermore, in order to prevent surface scratches during processing, assembly, testing, transportation, etc., a surface protection film is sometimes attached to the exposed surface of the reinforcing film before use. Such a surface protection film is peeled off from the reinforcing film when surface protection is no longer needed (Patent Document 2).

[0004] Such a reinforcing film may be attached to an optical member or an electronic member, and the optical member or the electronic member may be inspected through the reinforcing film.

[0005] However, when a reinforcing film is attached to an optical member or an electronic member and stored in a harsh environment for a long period of time, the reflectivity of the reinforcing film changes, and the detectability may be reduced.

[0006] As described above, in the reinforcing film that is pasted on optical components and electronic components and detects the optical components and electronic components through the reinforcing film, there is an aspect that needs to be improved, that is, when it is pasted on optical components and electronic components and stored for a long time in a harsh environment, it is important to suppress the change in the reflectivity of the reinforcing film.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent No. 6366199

[0010] Patent Document 2: Japanese Patent Application Publication No. 2016-17109 Summary of the invention

[0011] Problem that the invention aims to solve

[0012] The purpose of the subject of the present invention is to provide a reinforcing film, which is a reinforcing film that can be attached to an optical component or an electronic component, and when the optical component or the electronic component is detected through the reinforcing film, the change in reflectivity is suppressed and the detectability is not reduced. In addition, the purpose is to provide an optical component with a reinforcing film or an electronic component with a reinforcing film that has such a reinforcing film. Furthermore, the purpose is to provide a reinforcing film with a surface protective film that has a surface protective film on such a reinforcing film, and to provide a method for using such a reinforcing film with a surface protective film.

[0013] Solutions for solving problems

[0014] The reinforcing film according to the embodiment of the present invention is as follows:

[0015] A reinforcing film comprising a substrate layer A1 and an adhesive layer A2,

[0016] After the reinforcing film was stored in an environment of 60° C. and 90% RH for one week, the change rate of light reflectance at 580 nm was 2.0% or less.

[0017] In one embodiment, the haze change rate of the reinforcing film after being stored in an environment of 60° C. and 90% RH for one week is 10.0% or less.

[0018] In one embodiment, the total light transmittance of the base material layer A1 is 90% or more.

[0019] In one embodiment, in the reinforcing film according to the embodiment of the present invention, after the adhesive layer A2 is affixed to a PET film and left at 23° C. for 30 minutes, the adhesive strength to the PET film at a peeling angle of 180 degrees and a peeling speed of 300 mm / min is 0.30 N / 25 mm or more.

[0020] In one embodiment, the reinforcing film according to the embodiment of the present invention is attached to an adherend, and the adherend is an optical component or an electronic component.

[0021] An optical member with a reinforcing film or an electronic member with a reinforcing film according to an embodiment of the present invention includes the reinforcing film according to an embodiment of the present invention.

[0022] The reinforcing film with a surface protection film according to the embodiment of the present invention includes a surface protection film on the substrate layer A1 side of the reinforcing film according to the embodiment of the present invention.

[0023] In one embodiment, in the reinforcing film with a surface protection film according to an embodiment of the present invention, after the reinforcing film with a surface protection film is stored in an environment of 60° C. and 90% RH for 1 week, the light reflectance change rate of the reinforcing film at 580 nm after the surface protection film is peeled off is less than 5.0%.

[0024] The method of using the reinforcing film with a surface protection film of the present invention is as follows: the adhesive layer A2 of the reinforcing film with a surface protection film according to the embodiment of the present invention is exposed and the adhesive layer A2 is attached to an adherend, and then the surface protection film is peeled off.

[0025] Effects of the Invention

[0026] According to the present invention, a reinforcing film can be provided, which is a reinforcing film that can be attached to an optical component or an electronic component, and when the optical component or the electronic component is detected through the reinforcing film, the change in reflectivity is suppressed and the detectability is not reduced. In addition, an optical component with a reinforcing film or an electronic component with a reinforcing film that has such a reinforcing film can be provided. Furthermore, a reinforcing film with a surface protective film that has a surface protective film on such a reinforcing film can be provided, and a method for using such a reinforcing film with a surface protective film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic cross-sectional view of one embodiment of the reinforcing film in the embodiment of the present invention.

[0028] Figure 2 It is a schematic cross-sectional view of another embodiment of the reinforcing film in the embodiment of the present invention.

[0029] Figure 3 It is a schematic cross-sectional view of one embodiment of the surface protection film.

[0030] Figure 4 It is a schematic cross-sectional view of another embodiment of the surface protection film.

[0031] Figure 5 It is a schematic cross-sectional view of one embodiment of the reinforcing film with a surface protection film of the present invention. DETAILED DESCRIPTION

[0032] When "mass" is expressed in this specification, it can be interpreted as "weight" which is conventionally used as a general unit of weight. Conversely, when "weight" is expressed in this specification, it can be interpreted as "mass" which is conventionally used as an SI unit for expressing weight.

[0033] In this specification, the term "(meth)acrylic acid" means "acrylic acid and / or methacrylic acid", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein".

[0034] 《1. Reinforcement film》

[0035] The reinforcing film of the present invention comprises a substrate layer A1 and an adhesive layer A2. The reinforcing film of the present invention only needs to comprise the substrate layer A1 and the adhesive layer A2, and may comprise any other appropriate layer within a range not impairing the effects of the present invention.

[0036] For protection, a release sheet described later may be provided on the surface of the pressure-sensitive adhesive layer A2.

[0037] In order to impart various functions, a functional layer A3 described later may be provided on the surface of the base material layer A1.

[0038] The thickness of the reinforcing film may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 5 μm to 800 μm, more preferably 10 μm to 650 μm, further preferably 20 μm to 550 μm, and particularly preferably 25 μm to 450 μm.

[0039] In one embodiment of the reinforcing film, Figure 1 As shown, it is composed of a base material layer A1 (10) and an adhesive layer A2 (20).

[0040] For the reinforcing film of the present invention, the change rate of light reflectance at 580 nm after the reinforcing film is stored in an environment of 60° C. and 90% RH for one week is 2.0% or less, preferably 1.9% or less, more preferably 1.8% or less, further preferably 1.7% or less, and particularly preferably 1.6% or less. As long as the light reflectance change rate is within the above range, a reinforcing film can be provided in which the detectability is not reduced when optical components and electronic components are inspected through the reinforcing film.

[0041] For the reinforcing film of the present invention, the haze change rate after the reinforcing film is stored in an environment of 60°C and 90% RH for one week is preferably 10.0% or less, more preferably 7.0% or less, further preferably 6.0% or less, further preferably 5.0% or less, particularly preferably 4.0% or less, and most preferably 3.5% or less. As long as the haze change rate is within the above range, a reinforcing film can be provided in which the detectability is not further reduced when the optical component or electronic component is inspected through the reinforcing film.

[0042] <1-1. Base material layer A1>

[0043] As the substrate layer A1, a substrate formed of any suitable material can be used according to the purpose within the scope of not impairing the effect of the present invention. Such materials include, for example, resin sheets, nonwoven fabrics, paper, metal foil, woven fabrics, rubber sheets, foam sheets, and laminates thereof (particularly, laminates containing resin sheets).

[0044] Examples of the resin constituting the resin sheet include acrylic resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resins, polyetheretherketone (PEEK), and cyclic olefin polymers.

[0045] Examples of the nonwoven fabric include nonwoven fabrics made of heat-resistant natural fibers such as abaca nonwoven fabrics; synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabrics, polyethylene resin nonwoven fabrics, and ester resin nonwoven fabrics; and the like.

[0046] The base material layer A1 may be composed of only one layer or two or more layers.

[0047] The thickness of the substrate layer A1 may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 4 to 500 μm, more preferably 10 to 400 μm, further preferably 15 to 350 μm, and particularly preferably 20 to 300 μm.

[0048] The total light transmittance of the substrate layer A1 is preferably 90% or more, more preferably 91% or more, further preferably 92% or more, and particularly preferably 93% or more. As long as the total light transmittance of the substrate layer A1 is within the above range, a reinforcing film can be provided that does not further reduce the detectability when optical components and electronic components are inspected through the reinforcing film.

[0049] The base layer A1 may contain an antistatic agent. As the base layer A1 containing an antistatic agent, for example, a resin sheet kneaded with the antistatic agent may be used. Such a resin sheet may be formed from a composition for forming the base layer A1 containing a resin and an antistatic agent.

[0050] The base material layer A1 itself can also function as an antistatic agent. For example, when a metal foil is used as the material of the base material layer A1, the base material layer A1 itself can function as an antistatic agent.

[0051] The substrate layer A1 may be subjected to a surface treatment, such as corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, and primer coating treatment.

[0052] As organic coating materials, for example, materials described in Plastic Hard Coating Materials II (CMC Publishing, (2004)) can be cited. As such organic coating materials, preferably urethane polymers can be cited, and more preferably polyacrylic urethane, polyester urethane, or precursors thereof can be cited. The reason is that the coating / applying of the substrate layer A1 is simple, and a variety of materials can be selected in the industry and can be obtained cheaply. Such urethane polymers can be cited, for example, as polymers composed of a reaction mixture of an isocyanate monomer and an alcoholic hydroxyl-containing monomer (for example, a hydroxyl-containing acrylic compound or a hydroxyl-containing ester compound). The organic coating material may also contain chain extenders such as polyamines, antioxidants, oxidation stabilizers, etc. as arbitrary additives.

[0053] The base material layer A1 may contain any other appropriate additives according to the purpose, within a range not impairing the effects of the present invention.

[0054] <1-2. Adhesive Layer A2>

[0055] The thickness of the adhesive layer A2 may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 1 μm to 300 μm, more preferably 2 μm to 250 μm, further preferably 4 μm to 200 μm, and particularly preferably 5 μm to 150 μm.

[0056] The pressure-sensitive adhesive layer A2 may be composed of only one layer or two or more layers.

[0057] The adhesive layer A2 may contain a conductive component. The conductive component may be only one kind or two or more kinds.

[0058] After the adhesive layer A2 is adhered to a PET film and placed at 23°C for 30 minutes, the adhesion to the PET film at a peeling angle of 180 degrees and a peeling speed of 300 mm / min is preferably 0.30 N / 25 mm or more, more preferably 1 N / 25 mm to 40 N / 25 mm, further preferably 5 N / 25 mm to 35 N / 25 mm, and particularly preferably 10 N / 25 mm to 30 N / 25 mm.

[0059] After the adhesive layer A2 is adhered to a PET film and placed at 60°C for 60 minutes, the adhesion to the PET film at a peeling angle of 180 degrees and a peeling speed of 300 mm / min is preferably 10 N / 25 mm or more, more preferably 10 N / 25 mm to 40 N / 25 mm, further preferably 15 N / 25 mm to 35 N / 25 mm, and particularly preferably 20 N / 25 mm to 30 N / 25 mm.

[0060] Adhesive layer A2 is formed by adhesive composition a2. For adhesive layer A2, as long as the adhesive composition a2 can be formed into a layered method, any suitable method can be used to form. For example, the following method can be listed: for adhesive layer A2, adhesive composition a2 is applied to any suitable substrate, heated as required, active energy rays (ultraviolet rays, etc.) irradiated, dried, etc., and cured as required to form an adhesive layer on the substrate. As such a coating method, for example, a gravure roll coater, a reverse roll coater, a lick coater, a feed roll coater, a rod coater, a knife coater, an air knife coater, a sprayer, a comma coater, a direct coater, a roller brush coater, etc. can be listed.

[0061] From the viewpoint of further exhibiting the effects of the present invention, the adhesive composition a2 preferably contains a polymer component.

[0062] The polymer component is preferably at least one selected from an acrylic polymer, a urethane polymer, and a silicone polymer. The acrylic polymer will be described below as a representative example.

[0063] The acrylic polymer may be referred to as a base polymer in the field of acrylic pressure-sensitive adhesives. The acrylic polymer may be one type or two or more types.

[0064] The content ratio of the acrylic polymer in the adhesive composition a2 is preferably 60% to 99.999% by weight, more preferably 65% ​​to 99.99% by weight, further preferably 70% to 99.9% by weight, particularly preferably 75% to 99.9% by weight, and most preferably 80% to 99.9% by weight, calculated on a solid content basis.

[0065] As the acrylic polymer, any appropriate acrylic polymer can be adopted within a range not impairing the effects of the present invention.

[0066] From the viewpoint of further exhibiting the effects of the present invention, the weight average molecular weight of the acrylic polymer is preferably 300,000 to 2.5 million, more preferably 350,000 to 2 million, further preferably 400,000 to 1.8 million, and particularly preferably 500,000 to 1.5 million.

[0067] The acrylic polymer is preferably an acrylic polymer formed by polymerizing a composition (A) comprising (component a) an alkyl (meth)acrylate having an alkyl group with 4 to 12 carbon atoms in the alkyl ester moiety and (component b) at least one selected from the group consisting of a (meth)acrylate having an OH group and (meth)acrylic acid.

[0068] (a component) and (b component) may be used independently of each other alone or in combination of two or more.

[0069] Examples of the alkyl (meth)acrylate (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms include n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are more preferred, from the viewpoint of further exhibiting the effects of the present invention.

[0070] As at least one (component b) selected from the group consisting of (meth)acrylates and (meth)acrylic acid having an OH group, for example, (meth)acrylates having an OH group such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, (meth)acrylic acid, etc. can be cited. Among these, hydroxyethyl (meth)acrylate and (meth)acrylic acid are preferred, and hydroxyethyl acrylate and acrylic acid are more preferred, from the viewpoint of being able to further exhibit the effects of the present invention.

[0071] The composition (A) may also contain copolymerizable monomers other than the components (a) and (b). The copolymerizable monomers may be only one or more than one. Examples of such copolymerizable monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and alkyl (meth)acrylate esters having an alkyl group with 1 to 3 carbon atoms in the alkyl ester portion; carboxyl group-containing monomers such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and their anhydrides (for example, anhydride-containing monomers such as maleic anhydride and itaconic anhydride) (except for (meth)acrylic acid); (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-hydroxymethyl Amide-containing monomers such as 1,2-dimethyl (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide; amino-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; epoxy-containing monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; cyano-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone; Heterocyclic vinyl monomers such as pyrrolidinone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, vinylpyridine, vinylpyrimidine, vinyloxazole, etc.; sulfonic acid monomers such as sodium vinylsulfonate; phosphoric acid monomers such as 2-hydroxyethylacryloylphosphate; imide monomers such as cyclohexylmaleimide and isopropylmaleimide; isocyanate monomers such as 2-methacryloyloxyethyl isocyanate; cyclopentyl (meth)acrylate , cyclohexyl (meth)acrylate, isobornyl (meth)acrylate and other (meth)acrylates having alicyclic hydrocarbon groups; (meth)acrylates having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins and dienes such as ethylene, butadiene, isoprene and isobutylene; vinyl ethers such as vinyl alkyl ether; vinyl chloride; etc.

[0072] As copolymerizable monomers, multifunctional monomers can also be used. Multifunctional monomers refer to monomers having more than two ethylenically unsaturated groups in one molecule. As ethylenically unsaturated groups, any suitable ethylenically unsaturated groups can be used within the scope of not damaging the effect of the present invention. As such ethylenically unsaturated groups, for example, free radical polymerizable functional groups such as vinyl, propenyl, isopropenyl, vinyl ether (vinyloxy), allyl ether (allyloxy) can be listed. Examples of the multifunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. Such a multifunctional monomer may be used alone or in combination of two or more.

[0073] As the copolymerizable monomer, an alkoxyalkyl (meth)acrylate may also be used. Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The alkoxyalkyl (meth)acrylate may be one or more.

[0074] The content of the (meth)acrylic acid alkyl ester (component a) in which the alkyl group of the alkyl ester moiety has 4 to 12 carbon atoms is preferably 30% by weight or more, more preferably 35% to 99% by weight, further preferably 40% to 98% by weight, and particularly preferably 50% to 96% by weight, based on the total amount of monomer components constituting the acrylic polymer (100% by weight), from the viewpoint of further exhibiting the effects of the present invention.

[0075] The content of at least one (component b) selected from the group consisting of (meth)acrylates having an OH group and (meth)acrylic acid is preferably 1 wt% or more, more preferably 1 to 30 wt%, further preferably 2 to 20 wt%, and particularly preferably 3 to 15 wt%, based on the total amount (100 wt%) of the monomer components constituting the acrylic polymer, from the viewpoint of further exhibiting the effects of the present invention.

[0076] Composition (A) can contain any suitable other components within the scope of not damaging the effect of the present invention. As such other components, for example, polymerization initiator, chain transfer agent, solvent etc. can be listed. The content of these other components can adopt any suitable content within the scope of not damaging the effect of the present invention.

[0077] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), or the like, depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.

[0078] Thermal polymerization initiators can preferably be used when obtaining acrylic polymers by solution polymerization. As such thermal polymerization initiators, for example, azo polymerization initiators, peroxide polymerization initiators (for example, dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. can be cited. Among these thermal polymerization initiators, the azo initiators disclosed in Japanese Patent Publication No. 2002-69411 are particularly preferred. From the perspective that the part of the decomposition product of the polymerization initiator that becomes the cause of the generation of heated gas (outgassing) is not easy to remain in the acrylic polymer, such azo polymerization initiators are preferred. As azo polymerization initiators, 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis-4-cyanovaleric acid, etc. can be cited.

[0079] The photopolymerization initiator can be preferably used when obtaining an acrylic polymer by active energy ray polymerization. Examples of the photopolymerization initiator include benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators.

[0080] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and methyl anisole. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. As photoactive oxime-based photopolymerization initiators, for example, 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. can be listed. As benzoin-based photopolymerization initiators, for example, benzoin, etc. can be listed. As benzyl-based photopolymerization initiators, for example, benzyl, etc. can be listed. As benzophenone-based photopolymerization initiators, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, etc. can be listed. As ketal-based photopolymerization initiators, for example, benzyldimethylketal, etc. can be listed. As thioxanthone-based photopolymerization initiators, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc. can be listed.

[0081] The adhesive composition a2 may also contain a crosslinking agent. By using a crosslinking agent, the cohesive force of the acrylic adhesive can be improved, and the effect of the present invention can be further demonstrated. The crosslinking agent may be only one kind or two or more kinds.

[0082] As the crosslinking agent, in addition to polyfunctional isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, and peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. can also be listed. Among these, from the aspect that the effect of the present invention can be further exhibited, at least one (component c) selected from the group consisting of polyfunctional isocyanate crosslinking agents and epoxy crosslinking agents is preferred.

[0083] Examples of the polyfunctional isocyanate crosslinking agent include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4′-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of the polyfunctional isocyanate crosslinking agent include commercially available products such as trimethylolpropane / toluene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name “Coronate L”), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name “Coronate HL”), trade name “Coronate HX” (Nippon Polyurethane Industry Co., Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “TAKENATE 110N”).

[0084] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyol, Glycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule, etc. As epoxy crosslinking agents, commercial products such as the trade name "TETRAD C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.) can also be cited.

[0085] The content of the crosslinking agent in the adhesive composition a2 can be any suitable content within the range that does not impair the effect of the present invention. As such a content, for example, from the aspect of being able to further demonstrate the effect of the present invention, it is preferably 0.005 to 20 parts by weight, more preferably 0.05 to 18 parts by weight, further preferably 0.01 to 15 parts by weight, and particularly preferably 0.1 to 10 parts by weight relative to the solid content (100 parts by weight) of the acrylic polymer.

[0086] For adhesive composition a2, any suitable other components can be contained within the scope of not damaging the effect of the present invention. As such other components, for example, polymer components other than acrylic polymers, crosslinking accelerators, crosslinking catalysts, silane coupling agents, adhesion imparting resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antioxidants, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foils, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, conductive agents, stabilizers, surface lubricants, leveling agents, anticorrosives, heat stabilizers, inhibitors, lubricants, solvents, catalysts, etc. can be listed.

[0087] The adhesive composition a2 preferably does not contain an oligomer (X) obtained from a monomer composition containing an acrylic monomer having a cyclic structure of three or more rings as a main component. In this case, the content ratio of the acrylic monomer having a cyclic structure of three or more rings is preferably 50 parts by weight or more, more preferably 60 parts by weight to 99 parts by weight, further preferably 70 parts by weight to 98 parts by weight, and particularly preferably 80 parts by weight to 96 parts by weight, relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (X). By making the adhesive composition a2 free of an oligomer (X) obtained from a monomer composition containing an acrylic monomer having a cyclic structure of three or more rings as a main component, it is possible to provide a reinforcing film in which the detectability is not further reduced when optical components and electronic components are detected through the reinforcing film.

[0088] Examples of the acrylic monomer having a cyclic structure with three or more rings include dicyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentanyl methacrylate, dicyclopentanyloxyethyl methacrylate, dicyclopentanyloxyethyl acrylate, tricyclopentanyl methacrylate, tricyclopentanyl acrylate, 1-adamantyl methacrylate, 2-methyl-2-adamantyl methacrylate, 2-methyl-2-adamantyl acrylate, 2-ethyl-2-adamantyl methacrylate, and 2-ethyl-2-adamantyl acrylate.

[0089] The acrylic monomer having a cyclic structure of three or more rings may be used alone or in combination of two or more.

[0090] The monomer composition used to obtain the oligomer (X) may contain other monomers in addition to the acrylic monomer having a tricyclic or higher ring structure. Such other monomers may be present in only one type or in two or more types.

[0091] Examples of other monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates such as isodecyl acrylate; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; vinyl ester monomers such as vinyl acetate and vinyl propionate; hydroxyl-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylate monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; olefin monomers such as ethylene, propylene, isoprene, and butadiene; vinyl ether monomers such as vinyl ether; etc.

[0092] Other monomers include hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, hexyl di(meth)acrylate and other polyfunctional monomers.

[0093] Other monomers include nitrogen atom-containing monomers (for example, aminoalkyl (meth)acrylate monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; (N-substituted)amide monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-hydroxy (meth)acrylamide; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate, etc.).

[0094] The adhesive composition a2 may contain an oligomer (Y) other than the oligomer (X). However, from the viewpoint of further exhibiting the effects of the present invention, the content of the oligomer (Y) is preferably small.

[0095] From the perspective of further demonstrating the effects of the present invention, the content of the oligomer (Y) in the adhesive composition a2 is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, further preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less, relative to 100 parts by weight of the acrylic polymer contained in the adhesive composition a2.

[0096] The oligomer (Y) is preferably an oligomer obtained from a monomer composition containing an acrylic monomer having a bicyclic or shorter cyclic structure as a main component and 1 to 10 parts by weight of a carboxyl group-containing monomer based on 100 parts by weight of the total monomer component.

[0097] As the cyclic structure below the bicyclic ring, any of an aromatic ring and a non-aromatic ring may be used, but a non-aromatic ring is preferred. As the aromatic ring, for example, an aromatic hydrocarbon ring (for example, a condensed carbon ring in a benzene ring, naphthalene, etc.), various aromatic heterocyclic rings, etc. may be cited. As the non-aromatic ring, a non-aromatic alicyclic ring (cycloalkane rings such as a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, a cyclooctane ring; a cycloolefin ring such as a cyclohexene ring, etc.), a non-aromatic bridged ring (for example, a bicyclic hydrocarbon ring in pinane, pinene, camphane, norbornane, norbornene, etc.) may be cited.

[0098] Examples of the acrylic monomer having a cyclic structure of two or less rings include ethylenically unsaturated monomers having a cyclic structure in the molecule, such as cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate, aryl (meth)acrylates such as phenyl (meth)acrylate, aryloxyalkyl (meth)acrylates such as phenoxyethyl (meth)acrylate, arylalkyl (meth)acrylates such as benzyl (meth)acrylate, and styrene monomers such as styrene and α-methylstyrene.

[0099] As the acrylic monomer having a cyclic structure of two or less rings, preferably, (meth)acrylates having a non-aromatic ring such as cyclohexyl methacrylate and isobornyl (meth)acrylate are used, and cyclohexyl methacrylate is more preferably used from the viewpoint of transparency.

[0100] The acrylic monomer having a bicyclic or shorter cyclic structure may be used alone or in combination of two or more.

[0101] The content of the acrylic monomer having a cyclic structure of bicyclic or less is preferably 50 to 99 parts by weight, more preferably 70 to 99 parts by weight, further preferably 80 to 98 parts by weight, particularly preferably 90 to 97 parts by weight, and most preferably 92 to 96 parts by weight, relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (Y).

[0102] The oligomer (Y) may also include a carboxyl group-containing monomer as a monomer component. As such a carboxyl group-containing monomer, similarly to the carboxyl group-containing monomer that can constitute the acrylic polymer, for example, (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. may be listed. In addition, as a carboxyl group-containing monomer, anhydrides of these carboxyl group-containing monomers (for example, anhydride group-containing monomers such as maleic anhydride and itaconic anhydride) may also be listed.

[0103] The content of the carboxyl group-containing monomer is preferably 1 to 10 parts by weight, preferably 2 to 9 parts by weight, further preferably 3 to 8 parts by weight, and particularly preferably 4 to 7 parts by weight, relative to 100 parts by weight of all monomer components contained in the monomer composition used to obtain the oligomer (Y).

[0104] The monomer composition used to obtain the oligomer (Y) may contain other monomers in addition to the acrylic monomer having a bicyclic or shorter cyclic structure. Such other monomers may be present in one or more types.

[0105] Examples of other monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates such as isodecyl acrylate; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; vinyl ester monomers such as vinyl acetate and vinyl propionate; hydroxyl-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; alkoxyalkyl (meth)acrylate monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; olefin monomers such as ethylene, propylene, isoprene, and butadiene; vinyl ether monomers such as vinyl ether; etc.

[0106] Examples of other monomers include polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate, divinylbenzene, butyl di(meth)acrylate, and hexyl di(meth)acrylate.

[0107] Examples of other monomers include nitrogen atom-containing monomers (e.g., aminoalkyl (meth)acrylate monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; (N-substituted)amide monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-hydroxy (meth)acrylamide; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate, etc.). However, since such nitrogen atom-containing monomers may cause yellowing of the adhesive when heated, they are preferably not used when not needed.

[0108] Oligomer (X) and oligomer (Y) can be prepared by any suitable polymerization method within the scope of not impairing the effect of the present invention. As the polymerization method of acrylic polymer, for example, solution polymerization method, emulsion polymerization method, bulk polymerization method, polymerization method based on ultraviolet irradiation, etc. can be listed. From the perspective of transparency, water resistance, cost, etc., solution polymerization method is preferred.

[0109] Any appropriate polymerization initiator, chain transfer agent, and the like that can be used in the polymerization may be adopted within a range not impairing the effects of the present invention.

[0110] The amount of the polymerization initiator used may be any appropriate amount within a range that does not impair the effects of the present invention, and is preferably 0.1% by weight to 15% by weight based on the total amount of the monomer components.

[0111] The amount of the chain transfer agent used may be any appropriate amount within a range that does not impair the effects of the present invention, and is preferably 0.01% by weight to 15% by weight based on the total amount of the monomer components.

[0112] In the solution polymerization method, various common solvents can be used. Examples of such solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-pentane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and other organic solvents. The solvent may be only one kind or two or more kinds.

[0113] The weight average molecular weight of the oligomers (X) and (Y) is preferably 3,000 to 6,000, more preferably 3,300 to 5,500, and even more preferably 3,500 to 5,000.

[0114] The weight average molecular weight of the oligomers (X) and (Y) can be controlled by the type and amount of the polymerization initiator and chain transfer agent, the temperature and time during polymerization, as well as the monomer concentration, the monomer dropping speed, and the like.

[0115] When the adhesive composition a2 contains an acrylic polymer and an oligomer, as the ratio of the acrylic polymer to the oligomer, the oligomer is preferably 10 to 35 parts by weight, more preferably 15 to 30 parts by weight, relative to 100 parts by weight of the acrylic polymer. When the adhesive composition a2 contains an acrylic polymer and an oligomer, the effect of the present invention can be further exhibited as long as the ratio of the acrylic polymer to the oligomer is within the above range.

[0116] The adhesive composition a2 may contain known additives such as ultraviolet absorbers, antioxidants, light stabilizers, antioxidants, adhesion promoters, plasticizers, softeners, fillers, colorants (pigments, dyes, etc.), surfactants, antistatic agents, etc., as needed.

[0117] <1-3. Peel Sheet>

[0118] For protection, a release sheet may be provided on the surface of the pressure-sensitive adhesive layer A2. The release sheet may be a single layer or may be two or more layers.

[0119] From the viewpoint of further exhibiting the effects of the present invention, the thickness of the release sheet is preferably 5 μm to 300 μm, more preferably 10 μm to 200 μm, further preferably 10 μm to 150 μm, particularly preferably 10 μm to 130 μm, and most preferably 20 μm to 120 μm.

[0120] The release sheet includes a resin base film.

[0121] Examples of the resin substrate film include a plastic film made of a polyester resin such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); a plastic film made of an olefin resin having an α-olefin as a monomer component such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); a plastic film made of polyvinyl chloride (PVC); a plastic film made of a vinyl acetate resin; and a plastic film made of polycarbonate. Plastic films composed of (PC); plastic films composed of polyphenylene sulfide (PPS); plastic films composed of amide resins such as polyamide (nylon) and wholly aromatic polyamide (aramid); plastic films composed of polyimide resins; plastic films composed of polyetheretherketone (PEEK); plastic films composed of olefin resins such as polyethylene (PE) and polypropylene (PP); plastic films composed of fluorine resins such as polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer; etc.

[0122] The resin substrate film may be a single layer or may be a layer of two or more layers. The resin substrate film may be stretched.

[0123] The resin substrate film may be subjected to a surface treatment, such as corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, primer coating treatment, and the like.

[0124] The resin base film may contain any appropriate additives within a range not impairing the effects of the present invention.

[0125] The release sheet may have a release layer in order to improve the releasability from the adhesive layer A2. When the release sheet has a release layer, the release layer side is directly laminated on the adhesive layer A2.

[0126] Any suitable forming material can be used for the forming material of the release layer within the scope of not impairing the effect of the present invention. As such forming material, for example, silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, fatty acid amide-based release agents, etc. can be cited. Among these, silicone-based release agents are preferred. The release layer can be formed as a coating layer.

[0127] The thickness of the release layer may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 10 nm to 2000 nm, more preferably 10 nm to 1500 nm, further preferably 10 nm to 1000 nm, and particularly preferably 10 nm to 500 nm.

[0128] The release layer may be composed of only one layer or two or more layers.

[0129] Examples of the silicone release layer include addition reaction type silicone resins. Specifically, examples of addition reaction type silicone resins include KS-774, KS-775, KS-778, KS-779H, KS-847H, and KS-847T manufactured by Shin-Etsu Chemical Co., Ltd.; TPR-6700, TPR-6710, and TPR-6721 manufactured by Toshiba Silicone; and SD7220 and SD7226 manufactured by Dow Toray Co., Ltd. The coating amount of the silicone release layer (after drying) is preferably 0.01 g / m 2 ~2g / m 2 , more preferably 0.01 g / m 2 ~1g / m 2 , more preferably 0.01 g / m 2 ~0.5g / m 2 .

[0130] The release layer can be formed, for example, by applying the above-mentioned forming material on any suitable layer by a conventionally known coating method such as reverse gravure coating, bar coating, extrusion coating, and then curing it by heat treatment at about 120 to 200° C. Alternatively, heat treatment and active energy ray irradiation such as ultraviolet ray irradiation may be used in combination as required.

[0131] The release sheet may also have an antistatic layer.

[0132] The thickness of the antistatic layer may be any appropriate thickness within the range not impairing the effects of the present invention, and is preferably 1 nm to 1000 nm, more preferably 5 nm to 900 nm, further preferably 7.5 nm to 800 nm, and particularly preferably 10 nm to 700 nm.

[0133] The antistatic layer may be only one layer or may be two or more layers.

[0134] As antistatic layer, as long as it is a layer that can play an antistatic effect, any suitable antistatic layer can be adopted within the scope of not damaging the effect of the present invention. As such antistatic layer, it is preferably an antistatic layer formed by coating a conductive coating liquid comprising a conductive polymer on any suitable substrate layer. Specifically, for example, an antistatic layer formed by coating a conductive coating liquid comprising a conductive polymer on a resin substrate film. As a specific coating method, roll coating, rod coating, gravure coating, etc. can be listed.

[0135] As the conductive polymer, any suitable conductive polymer can be used within the scope of not damaging the effect of the present invention. As such a conductive polymer, for example, conductive polymers doped with polyanions in π-conjugated conductive polymers can be listed. As π-conjugated conductive polymers, chain conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene can be listed. As polyanions, polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, polymethacrylic acid, etc. can be listed. The conductive polymer can be only one kind, or it can be more than two kinds.

[0136] <1-4. Functional layer A3>

[0137] The reinforcing film may include a functional layer A3, a substrate layer A1 and an adhesive layer A2 in sequence. That is, in another embodiment of the reinforcing film, Figure 2 As shown, it is composed of a functional layer A3 (30), a base material layer A1 (10) and an adhesive layer A2 (20).

[0138] The functional layer A3 is a layer that is optionally provided and can impart various functions to the reinforcing film.

[0139] The thickness of the functional layer A3 may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 1 nm to 1000 nm, more preferably 2 nm to 800 nm, further preferably 5 nm to 400 nm, and particularly preferably 10 nm to 200 nm.

[0140] The functional layer A3 may be only one layer or may be two or more layers.

[0141] As functional layer A3, in the scope that does not damage effect of the present invention, can adopt any suitable functional layer.As such functional layer, for example can enumerate antistatic layer, antireflection layer, antiglare layer, hard coat etc., from can further show effect of the present invention aspect consideration, can select antireflection layer.

[0142] As the anti-reflection layer, any suitable anti-reflection layer can be adopted within the range that does not impair the effect of the present invention. As such an anti-reflection layer, for example, the anti-reflection layer described in Japanese Patent Laid-Open No. 2019-144577 can be cited.

[0143] As the functional layer A3, an antistatic layer may be appropriately selected in order to exhibit an antistatic effect.

[0144] When both an antireflection layer and an antistatic layer are selected as the functional layer A3, the antistatic layer is preferably disposed on the substrate layer A1 side from the viewpoint that the function of the antireflection layer can be further exhibited.

[0145] As an antistatic layer, as long as it is a layer that can exert an antistatic effect, any suitable antistatic layer can be adopted within the scope of not damaging the effect of the present invention. As such an antistatic layer, it is preferably an antistatic layer formed by applying a conductive coating liquid comprising a conductive polymer on any suitable substrate layer. Specifically, for example, an antistatic layer formed by applying a conductive coating liquid comprising a conductive polymer on substrate layer A1. As a specific coating method, roll coating, rod coating, gravure coating, etc. can be listed.

[0146] As the conductive polymer, any suitable conductive polymer can be used within the scope of not damaging the effect of the present invention. As such a conductive polymer, for example, a conductive polymer doped with a polyanion in a π-conjugated conductive polymer can be cited. As the π-conjugated conductive polymer, chain conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene can be cited. As the polyanion, polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyethyl acrylate sulfonic acid, polymethacrylic acid, etc. can be cited.

[0147] <1-5. Use of reinforcing film, optical component with reinforcing film, electronic component with reinforcing film>

[0148] The reinforcing film of the present invention is affixed to an adherend, and the adherend is any suitable component. Representatively, the reinforcing film of the present invention is affixed to an adherend, and the adherend is an optical component or an electronic component. In this case, the exposed surface side of the adhesive layer A2 of the reinforcing film of the present invention is affixed to an adherend, and the adherend is an optical component or an electronic component. In this way, an optical component with a reinforcing film or an electronic component with a reinforcing film of the present invention can be obtained. That is, the optical component with a reinforcing film of the present invention or the electronic component with a reinforcing film has the reinforcing film of the present invention.

[0149] 《2. Surface protection film》

[0150] The surface protection film is disposed on the substrate layer A1 side of the reinforcing film. When the substrate layer A1 has the functional layer A3, the surface protection film is disposed on the functional layer A3 side.

[0151] The thickness of the surface protection film may be any suitable thickness according to the purpose within the range not impairing the effect of the present invention, and is preferably 4 μm to 500 μm, more preferably 10 μm to 400 μm, further preferably 15 μm to 350 μm, and particularly preferably 20 μm to 300 μm.

[0152] The surface protection film includes a base material layer B1 and an adhesive layer B2. As long as the surface protection film includes the base material layer B1 and the adhesive layer B2, it may include any other appropriate layer within a range that does not impair the effects of the present invention.

[0153] For protection, a release sheet may be provided on the surface of the pressure-sensitive adhesive layer B2.

[0154] In order to impart various functions, a functional layer B3 may be provided on the surface of the base layer B1.

[0155] The thickness of the surface protection film may be any suitable thickness according to the purpose within the range not impairing the effect of the present invention, and is preferably 5 μm to 500 μm, more preferably 10 μm to 450 μm, further preferably 15 μm to 400 μm, and particularly preferably 20 μm to 300 μm.

[0156] like Figure 3 As shown, one embodiment of the surface protection film is composed of a base material layer B1 (40), an adhesive layer B2 (50) and a release sheet (60).

[0157] like Figure 4 As shown, one embodiment of the surface protection film is composed of a functional layer B3 (70), a base layer B1 (40), an adhesive layer B2 (50) and a release sheet (60).

[0158] <2-1. Base material layer B1>

[0159] As the base material layer B1, a base material formed of any appropriate material can be adopted according to the purpose within the range not impairing the effects of the present invention. Examples of such a material include the materials exemplified in the item <1-1. Base material layer A1>.

[0160] The base material layer B1 may be composed of only one layer or two or more layers.

[0161] The thickness of the substrate layer B1 may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 4 to 350 μm, more preferably 8 to 325 μm, further preferably 12 to 290 μm, and particularly preferably 15 to 205 μm.

[0162] The base layer B1 may contain an antistatic agent. As the base layer B1 containing an antistatic agent, for example, a resin sheet kneaded with the antistatic agent may be used. Such a resin sheet may be formed from a composition for forming the base layer B1 containing a resin and an antistatic agent.

[0163] The base layer B1 itself can also function as an antistatic agent. For example, when a metal foil is used as the material of the base layer B1, the base layer B1 itself can function as an antistatic agent.

[0164] The substrate layer B1 may be subjected to a surface treatment, such as corona treatment, plasma treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, and primer coating treatment.

[0165] Examples of the organic coating material include the materials exemplified in the item <1-1. Base material layer A1>.

[0166] The base material layer B1 may contain any other appropriate additives according to the purpose, within a range not impairing the effects of the present invention.

[0167] <2-2. Adhesive layer B2>

[0168] The thickness of the adhesive layer B2 may be any suitable thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 1 μm to 150 μm, more preferably 2 μm to 125 μm, further preferably 3 μm to 110 μm, and particularly preferably 5 μm to 95 μm.

[0169] As the adhesive layer B2, an adhesive layer composed of any suitable adhesive can be used within the scope of not impairing the effect of the present invention. As such an adhesive, for example, an adhesive constituting an adhesive layer described in Japanese Patent Publication No. 2019-127526 can be listed, and preferably at least one selected from the group consisting of acrylic adhesives, urethane adhesives, and silicone adhesives described in the publication is listed.

[0170] <2-3. Peel Sheet>

[0171] For protection, a release sheet may be provided on the surface of the pressure-sensitive adhesive layer B2. The release sheet may be a single layer or may be two or more layers.

[0172] Regarding the release sheet which the surface protection film may have, the description in the section <1-3. Release sheet> can be cited.

[0173] <2-4. Functional layer B3>

[0174] The surface protection film may include a functional layer B3, a base layer B1, and an adhesive layer B2 in this order.

[0175] The functional layer B3 is a layer that is optionally provided and can impart various functions to the reinforcing film.

[0176] The thickness of the functional layer B3 may be any appropriate thickness according to the purpose within the range not impairing the effects of the present invention, and is preferably 1 nm to 1000 nm, more preferably 2 nm to 800 nm, further preferably 5 nm to 400 nm, and particularly preferably 10 nm to 200 nm.

[0177] The functional layer B3 may be only one layer or may be two or more layers.

[0178] For the functional layer B3, the description in the item <1-4. Functional layer A3> can be cited.

[0179] 《3. Reinforcement film with surface protection film》

[0180] The reinforcing film with a surface protection film of the present invention has a surface protection film on the substrate layer A1 side of the reinforcing film of the present invention. When the reinforcing film of the present invention further has a functional layer A3 on the substrate layer A1, the surface protection film is provided on the surface of the functional layer A3.

[0181] The reinforcing film with a surface protection film of the present invention comprises a reinforcing film and a surface protection film. The reinforcing film with a surface protection film of the present invention may have any other suitable layers within the range not impairing the effects of the present invention as long as it comprises a reinforcing film and a surface protection film.

[0182] In the reinforcing film with a surface protection film of the present invention, the reinforcing film includes a base material layer A1 and an adhesive layer A2, and the surface protection film includes a base material layer B1 and an adhesive layer B2.

[0183] The thickness of the reinforcing film with a surface protection film of the present invention can be any suitable thickness according to the purpose within the range that does not impair the effect of the present invention. Such a thickness is preferably 9 μm to 1300 μm, more preferably 20 μm to 1050 μm, further preferably 35 μm to 900 μm, and particularly preferably 45 μm to 750 μm.

[0184] The reinforcing film with a surface protection film of the present invention can be obtained by laminating the reinforcing film and the surface protection film directly on the substrate layer A1 (when the substrate layer A1 further has a functional layer A3, the functional layer A3) and the adhesive layer B2 of the surface protection film (when a release sheet is provided on the adhesive layer B2, the adhesive layer B2 exposed by peeling off the release sheet) to obtain the reinforcing film.

[0185] like Figure 5 As shown, one embodiment of the reinforcing film with a surface protection film of the present invention is as follows: a reinforcing film composed of a substrate layer A1 (10) and an adhesive layer A2 (20), and a surface protection film composed of a substrate layer B1 (40) and an adhesive layer B2 (50) are directly laminated on the substrate layer A1 (10) and the adhesive layer B2 (50) for bonding.

[0186] For the reinforcing film with a surface protection film of the present invention, after the reinforcing film with a surface protection film is stored for 1 week under an environment of 60° C. and 90% RH, the light reflectance change rate of the reinforcing film at 580 nm after the surface protection film is peeled off is preferably 5.0% or less, more preferably 4.8%, more preferably 4.5%, more preferably 4.2%, more preferably 4.0%, particularly preferably 3.7%, and most preferably 3.5%. As long as the light reflectance change rate is within the above range, a reinforcing film can be provided in which the detectability is not reduced when optical components and electronic components are detected through the reinforcing film.

[0187] 《4. Usage of reinforcing film》

[0188] The reinforcing film of the present invention is typically attached to an adherend, which is an optical component or an electronic component. Specifically, the exposed surface of the adhesive layer A2 of the reinforcing film of the present invention is attached to an adherend, which is an optical component or an electronic component. When a release sheet is provided on the surface of the adhesive layer A2, the adhesive layer A2 exposed by peeling off the release sheet is attached to the adherend, which is an optical component or an electronic component.

[0189] The adherend is an optical member or an electronic member, and examples thereof include LED, micro LED, mini LED, and OLED. Representative examples of such adherends include OLED.

[0190] From the viewpoint of making fuller use of the effect of the reinforcing film of the present invention, the OLED is preferably at least one selected from the group consisting of a foldable member, a flexible member, and a rollable member.

[0191] An accordion member is a (foldable) member having a movable bending portion, a flexible member is a bendable member, and a rollable member is a rollable member.

[0192] 《5. How to use the reinforcing film with a surface protection film》

[0193] The method for using the laminated film with a surface protective film of the present invention is as follows: the adhesive layer A2 of the reinforcing film with a surface protective film of the present invention is exposed and the adhesive layer A2 is attached to an adherend, and then the surface protective film is peeled off. In the reinforcing film with a surface protective film of the present invention, when a release sheet is provided on the surface of the adhesive layer A2, first, the release sheet is peeled off to expose the adhesive layer surface on one side of the adhesive layer A2, and the adhesive layer surface is attached to an adherend. Then, the surface protective film is peeled off.

[0194] In this manner, a member in which the reinforcing film is attached to an adherend can be obtained.

[0195] Example

[0196] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that the test and evaluation methods in the examples are as follows. It should be noted that when "parts" are recorded, they refer to "parts by weight" unless otherwise stated, and when "%" are recorded, they refer to "% by weight" unless otherwise stated.

[0197] <Measurement of Weight Average Molecular Weight>

[0198] The weight average molecular weight was measured by gel permeation chromatography (GPC). Specifically, a GPC measuring apparatus was used, trade name "HLC-8120GPC" (manufactured by Tosoh Corporation), and the measurement was performed under the following conditions, and the weight average molecular weight was calculated based on the standard polystyrene conversion value.

[0199] (Molecular weight measurement conditions)

[0200] Sample concentration: 0.2 wt% (tetrahydrofuran solution)

[0201] Sample injection volume: 10μL

[0202] · Column: Trade name "TSKguardcolumn SuperHZ-H (1 piece) + TSKgel SuperHZM-H (2 pieces)" (manufactured by Tosoh Corporation)

[0203] ·Reference column: Trade name "TSKgel SuperH-RC (1 column)" (manufactured by Tosoh Corporation)

[0204] ·Eluent: Tetrahydrofuran (THF)

[0205] Flow rate: 0.6mL / min

[0206] Detector: Differential Refractometer (RI)

[0207] Column temperature (measurement temperature): 40°C

[0208] <Light reflectance change (without surface protection film)>

[0209] The release sheet was peeled off from the reinforcing film obtained in the embodiment or comparative example, and the adhesive surface of the reinforcing film was attached to a black acrylic plate with a thickness of 1 mm. The light reflectance from the substrate side at 580 nm was measured using a spectrophotometer (manufactured by Hitachi, Ltd., model: U-4100) to obtain the light reflectance R1 (%). Next, the reinforcing film obtained in the embodiment or comparative example was stored in an environment of 60°C and 90% RH for 1 week, and then placed at 23°C for 30 minutes to return to room temperature. After the release sheet was peeled off, the adhesive surface of the reinforcing film remaining was attached to a black acrylic plate with a thickness of 1 mm in the same manner, and the light reflectance from the substrate side at 580 nm was measured to obtain the light reflectance R2 (%). Using the obtained light reflectance value, the change rate of light reflectance (light reflectance change rate) ΔR (%) = (R2-R1) / (R1)×100 was calculated. It should be noted that if the black acrylic plate is a black resin plate, it will not affect the measured value, so other black resin plates may also be used.

[0210] <Light reflectance change rate (with surface protection film)>

[0211] The release sheet was peeled off from the reinforcing film obtained in the examples or comparative examples, and the adhesive surface of the reinforcing film was attached to a black acrylic plate with a thickness of 1 mm. The light reflectance from the substrate side at 580 nm was measured using a spectrophotometer (manufactured by Hitachi, Ltd., model: U-4100), and the light reflectance R1 (%) was obtained. Next, the laminate of the reinforcing film and the surface protection film obtained in the corresponding examples or comparative examples (reinforcing film with surface protection film) was stored in an environment of 60° C. and 90% RH for 1 week, and then placed at 23° C. for 30 minutes to return to room temperature. After the surface protection film and the release sheet were peeled off, the adhesive surface of the reinforcing film remaining was attached to a black acrylic plate with a thickness of 1 mm, and the light reflectance from the substrate side at 580 nm was measured to obtain the light reflectance R2 (%). Using the obtained light reflectance value, the change rate of light reflectance (light reflectance change rate) ΔR (%) = (R2-R1) / (R1) × 100 is calculated. It should be noted that if the black acrylic plate is a black resin plate, it will not affect the measured value, so other black resin plates can also be used.

[0212] <Haze change rate>

[0213] The release sheet was peeled off from the reinforcing film obtained in the examples or comparative examples, and the haze was measured using a haze meter (manufactured by Murakami Color Co., Ltd., model: HM-150) to obtain the haze H1 (%). Next, the reinforcing film obtained in the examples or comparative examples was stored in an environment of 60°C and 90% RH for 1 week, and then allowed to stand at 23°C for 30 minutes to return to room temperature. After the release sheet was peeled off, the haze of the remaining reinforcing film was measured in the same manner to obtain the haze H2 (%). Using the obtained haze value, the haze change rate ΔH (%) = (H2-H1) / (H1)×100 was calculated.

[0214] <Total light transmittance>

[0215] The transmittance of the substrate layer used in Examples or Comparative Examples at 580 nm was measured using a spectrophotometer (manufactured by Hitachi, Ltd., model: U-4100).

[0216] <Adhesion to PET film>

[0217] The reinforcing film (25 mm width×140 mm length) from which the release sheet was peeled was attached to a glass-lined PET film “Lumirror S10#25” (manufactured by Toray Industries, Inc.) by reciprocating once with a 2 kg hand roller and then left at an ambient temperature of 23° C. for 30 minutes.

[0218] The evaluation sample obtained as described above was measured using a tensile testing machine. As a tensile testing machine, a product name "Autograph AG-Xplus HS 6000mm / min high-speed type (AG-50NXplus)" manufactured by Shimadzu Corporation was used. After the evaluation sample was installed in the tensile testing machine, the tensile test was started. The conditions of the tensile test were as follows: peeling angle: 180 degrees, peeling speed (tensile speed): 300mm / min. The load when peeling the reinforcing film from the above-mentioned PET film was measured, and the average load at this time was used as the adhesion of the reinforcing film to the PET film.

[0219] <Adhesion to PET film (after heating at 60°C for 60 minutes)>

[0220] The reinforcing film (25 mm width×140 mm length) from which the release sheet was peeled was attached to a glass-lined PET film “Lumirror S10#25” (manufactured by Toray Industries, Inc.) by reciprocating once with a 2 kg hand roller and then left at an ambient temperature of 60° C. for 60 minutes.

[0221] The evaluation sample obtained as described above was measured using a tensile testing machine. As a tensile testing machine, a product name "Autograph AG-Xplus HS 6000mm / min high-speed type (AG-50NXplus)" manufactured by Shimadzu Corporation was used. After the evaluation sample was installed in the tensile testing machine, the tensile test was started. The conditions of the tensile test were as follows: peeling angle: 180 degrees, peeling speed (tensile speed): 300mm / min. The load when peeling the reinforcing film from the above-mentioned PET film was measured, and the average load at this time was used as the adhesion of the reinforcing film to the PET film.

[0222] [Production Example 1] Production of (meth)acrylic acid polymer (1)

[0223] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser, 65 parts of 2-ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 15 parts of N-vinyl pyrrolidone (manufactured by Nippon Shokubai Co., Ltd.), 13 parts of hydroxyethyl acrylate (manufactured by Toagosei Co., Ltd.), 7 parts of methyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were placed, and nitrogen was introduced while slowly stirring. The temperature of the liquid in the flask was maintained at about 63° C., and a polymerization reaction was carried out for 10 hours to prepare a solution of a (meth)acrylic acid polymer (1) having a weight average molecular weight of 700,000 (solid content concentration = 40% by weight).

[0224] [Production Example 2] Production of (meth)acrylic acid polymer (2)

[0225] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser, 100 parts of butyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 7.5 parts of acrylic acid (manufactured by Toagosei Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were placed, and nitrogen was introduced while slowly stirring. The temperature of the liquid in the flask was maintained at about 63°C, and a polymerization reaction was carried out for 10 hours to prepare a solution of a (meth)acrylic acid polymer (2) having a weight average molecular weight of 700,000 (solid content concentration = 40% by weight).

[0226] [Production Example 3] Production of (meth)acrylic acid polymer (3)

[0227] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser, 96 parts of 2-ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.), 4 parts of hydroxyethyl acrylate (manufactured by Toagosei Co., Ltd.), 0.2 parts of 2,2'-azobisisobutyronitrile (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 156 parts by weight of ethyl acetate were placed, and nitrogen was introduced while slowly stirring. The temperature of the liquid in the flask was maintained at about 63°C, and a polymerization reaction was carried out for 10 hours to prepare a solution of a (meth)acrylic acid polymer (3) having a weight average molecular weight of 500,000 (solid content concentration = 40% by weight).

[0228] [Production Example 4] Production of (meth)acrylic acid oligomer (4)

[0229] Cyclohexyl methacrylate as a monomer component [glass transition temperature of homopolymer (polycyclohexyl methacrylate): 66°C]: 95 parts by weight, acrylic acid: 5 parts by weight, 2-mercaptoethanol as a chain transfer agent: 3 parts by weight, 2,2′-azobisisobutyronitrile as a polymerization initiator: 0.2 parts by weight, and toluene as a polymerization solvent: 103.2 parts by weight were placed in a separable flask, and stirred for 1 hour while introducing nitrogen. In this way, after removing oxygen in the polymer system, the temperature was raised to 70°C and reacted for 3 hours, and further reacted at 75°C for 2 hours to prepare a solution of a (meth)acrylic oligomer (4) having a weight average molecular weight of 4000 (solid content concentration = 50% by weight).

[0230] [Production Example 5] Production of (meth)acrylic acid oligomer (5)

[0231] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, a condenser, and a dropping funnel, 100 parts by weight of toluene, 60 parts by weight of dicyclopentyl methacrylate (DCPMA) (trade name: FA-513M, manufactured by Hitachi Chemical Co., Ltd.), 40 parts by weight of methyl methacrylate (MMA), and 3.5 parts by weight of methyl thioglycolate as a chain transfer agent were placed. Furthermore, after stirring at 70°C for 1 hour in a nitrogen atmosphere, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added, and the mixture was reacted at 70°C for 2 hours, then at 80°C for 4 hours, and then at 90°C for 1 hour to prepare a solution of a (meth)acrylic oligomer (5) having a weight average molecular weight of 4000 (solid content concentration = 51% by weight).

[0232] [Production Example 6] Production of (meth)acrylic acid oligomer (6)

[0233] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, a condenser, and a dropping funnel, 100 parts by weight of toluene, 40 parts by weight of methyl methacrylate (MMA), 20 parts by weight of butyl methacrylate (BMA), 20 parts by weight of 2-ethylhexyl methacrylate (2-EHMA), 17 parts by weight of a methacrylate monomer containing a polyorganosiloxane skeleton having a functional group equivalent of 900 g / mol (trade name: X-22-174ASX, manufactured by Shin-Etsu Chemical Co., Ltd.), 3 parts by weight of a methacrylate monomer containing a polyorganosiloxane skeleton having a functional group equivalent of 4600 g / mol (trade name: X-22-174DX, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.51 parts by weight of methyl thioglycolate as a chain transfer agent were charged. Furthermore, after stirring at 70°C for 1 hour in a nitrogen atmosphere, 0.2 parts by weight of azobisisobutyronitrile as a thermal polymerization initiator was added, and after reacting at 70°C for 2 hours, 0.1 parts by weight of azobisisobutyronitrile as a thermal polymerization initiator was added, followed by reacting at 80°C for 5 hours to prepare a solution of a (meth)acrylic oligomer (6) having a weight average molecular weight of 21,300 (solid content concentration = 50% by weight).

[0234] [Production Example 7] Production of (meth)acrylic adhesive composition (1)

[0235] To the solution of the (meth)acrylic polymer (1) obtained in Production Example 1, 1.0 part by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent was added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (1).

[0236] [Production Example 8] Production of (meth)acrylic adhesive composition (2)

[0237] To the solution of the (meth)acrylic polymer (2) obtained in Production Example 2, 0.075 parts by weight of TETRAD-C (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent, in terms of solid content, and 20 parts by weight of the solution of the (meth)acrylic oligomer (4) obtained in Production Example 4, in terms of solid content, were added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (2). The solution was diluted with ethyl acetate so that the total solid content became 25% by weight, and the mixture was stirred using a disperser to prepare a (meth)acrylic adhesive composition (2).

[0238] [Production Example 9] Production of (meth)acrylic adhesive composition (3)

[0239] To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, and 5 parts by weight of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5, in terms of solid content, were added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (3).

[0240] [Production Example 10] Production of (meth)acrylic adhesive composition (4)

[0241] To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, in terms of solid content, and 7.5 parts by weight of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5, in terms of solid content, were added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (4).

[0242] [Production Example 11] Production of (meth)acrylic adhesive composition (5)

[0243] To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 0.1 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, in terms of solid content, and 10 parts by weight of the solution of the (meth)acrylic oligomer (5) obtained in Production Example 5, in terms of solid content, were added, the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and the mixture was stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (5).

[0244] [Production Example 12] Production of (meth)acrylic adhesive composition (6)

[0245] To the solution of the (meth)acrylic polymer (3) obtained in Production Example 3, 4.0 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent was added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (3), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (6).

[0246] [Production Example 13] Production of (meth)acrylic adhesive composition (7)

[0247] To the solution of the (meth)acrylic polymer (1) obtained in Production Example 1, 1.0 part by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, in terms of solid content, and 2.0 parts by weight of the solution of the (meth)acrylic oligomer (6) obtained in Production Example 6, in terms of solid content, were added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (7).

[0248] [Production Example 14] Production of (meth)acrylic adhesive composition (8)

[0249] To the solution of the (meth)acrylic polymer (1) obtained in Production Example 1, 2.5 parts by weight of Coronate HL (manufactured by Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent, in terms of solid content, and 2.5 parts by weight of the solution of the (meth)acrylic oligomer (6) obtained in Production Example 6, in terms of solid content, were added based on 100 parts by weight of the solid content of the solution of the (meth)acrylic polymer (1), and the mixture was diluted with ethyl acetate so that the total solid content became 25% by weight, and stirred using a disperser to prepare a (meth)acrylic pressure-sensitive adhesive composition (8).

[0250] [Manufacturing Example 15] Manufacture of coating composition for forming antireflection layer

[0251] In a 200 mL glass container, 60 g of ethanol, 30 g of a water-dispersed sol of ZnO fine particles (average primary particle size: 20 nm, average aggregate particle size: 40 nm, solid content conversion concentration: 20 wt%), and 10 g of tetraethoxysilane (SiO2 solid content concentration: 29 wt%) were placed, and an aqueous ammonia solution was added to set the pH to 10. The mixture was stirred at 20°C for 6 hours to obtain a dispersion of core-shell particles (solid content concentration: 6 wt%): 100 g. 100 g of a strongly acidic cation exchange resin (total exchange capacity: 2.0 meq / mL or more) was added to the obtained dispersion of core-shell particles: 100 g, and after stirring for 1 hour until the pH was 4, the strongly acidic cation exchange resin was removed by filtration to obtain a dispersion of spherical hollow fine particles composed of SiO2. The obtained dispersion was concentrated to a solid content concentration of 20 wt% by ultrafiltration. The spherical hollow fine particles were secondary aggregated. The shell thickness of the spherical hollow fine particles was 5 nm, which was 1 / 6 of the average primary particle size. The average aggregate particle size of the spherical hollow fine particles was 40 nm, and the aspect ratio was 1.0.

[0252] In a 200 mL glass container, 2 g of the obtained dispersion of spherical hollow particles (solid content concentration: 20 wt%), 2 g of a dispersion of fibrous solid particles (manufactured by Nissan Chemical Industries, Ltd., IPA-ST-UP, average aggregate particle size (average primary particle size): 90 nm, aspect ratio: 7.0, solid content concentration: 15 wt%), 90 g of ethanol, and 6 g of a silicate oligomer solution (solid content concentration: 5 wt%) were placed and stirred for 10 minutes to obtain a coating composition for forming an anti-reflection layer.

[0253] [Manufacturing Example 16] Manufacture of TAC film substrate (A) having an antireflection layer

[0254] The coating composition for forming an antireflection layer obtained in Production Example 15 was applied to one side of a cellulose triacetate (hereinafter sometimes referred to as "TAC") film (TG60UL, manufactured by FUJIFILM Corporation), and after spin coating at a rotation speed of 200 rpm for 60 seconds and homogenization, it was dried at 200° C. for 30 minutes to form an antireflection layer having a film thickness of 100 nm. In this way, a cellulose triacetate film substrate having an antireflection layer was obtained.

[0255] [Manufacturing Example 17] Manufacture of PET film substrate (B) having an antireflection layer

[0256] The coating composition for forming an antireflection layer obtained in Preparation Example 15 was applied to one side of a polyethylene terephthalate (hereinafter sometimes referred to as "PET") film (Lumirror U48, manufactured by Toray Industries, Inc.), and after spin coating at a rotation speed of 200 rpm for 60 seconds and homogenization, it was dried at 200° C. for 30 minutes to form an antireflection layer with a film thickness of 100 nm. In this way, a polyethylene terephthalate film substrate having an antireflection layer was obtained.

[0257] [Manufacturing Example 18]: Manufacture of surface protection film (C)

[0258] The (meth) acrylic adhesive composition (7) obtained in Manufacturing Example 13 was applied to a substrate formed of a polyester resin (trade name: "Lumirror S10", thickness 38 μm, manufactured by Toray Industries, Inc.) using a feed roller in a manner to have a thickness of 21 μm after drying, and cured and dried under the conditions of a drying temperature of 130° C. and a drying time of 30 seconds. In this way, an adhesive layer was prepared on the substrate. Next, the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) composed of a polyester resin with a thickness of 25 μm and a silicone treatment on one side was bonded to the surface of the obtained adhesive layer to obtain a surface protection film (C). The obtained surface protection film (C) was aged at room temperature for 7 days.

[0259] [Example 1]

[0260] The (meth)acrylic adhesive composition (1) is applied to the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) composed of a polyester resin with a thickness of 25 μm and a silicone treatment on one side in a manner of 25 μm after drying, and cured and dried under the conditions of a drying temperature of 130°C and a drying time of 3 minutes. In this way, an adhesive layer formed by the (meth)acrylic adhesive composition (1) is provided on the silicone-treated surface. Next, the surface of the TAC film substrate (A) having an anti-reflection layer on which the anti-reflection layer is not applied is attached to the surface of the obtained adhesive layer to obtain a reinforcing film (1). The obtained reinforcing film (1) is aged at room temperature for 7 days. The results are shown in Table 1.

[0261] [Example 2]

[0262] As shown in Table 1, a reinforcing film (2) was obtained in the same manner as in Example 1 except that the substrate was changed to a PET film substrate (B) having an antireflection layer.

[0263] [Example 3]

[0264] As shown in Table 1, a reinforcing film (3) was obtained in the same manner as in Example 1 except that the substrate was changed to a TAC film (TG60UL, manufactured by FUJIFILM Corporation).

[0265] [Example 4]

[0266] As shown in Table 1, a reinforcing film (4) was obtained in the same manner as in Example 1 except that the substrate was changed to a PET film (Lumirror U48, manufactured by Toray Industries, Inc.).

[0267] [Example 5]

[0268] As shown in Table 1, a reinforcing film (5) was obtained in the same manner as in Example 1 except that the substrate was changed to a polyimide (hereinafter sometimes referred to as "PI") film (Neoprene S-100, manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0269] [Example 6]

[0270] As shown in Table 1, a reinforcing film (6) was obtained in the same manner as in Example 1 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (2).

[0271] [Example 7]

[0272] As shown in Table 1, a reinforcing film (7) was obtained in the same manner as in Example 2 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (2).

[0273] [Example 8]

[0274] As shown in Table 1, a reinforcing film (8) was obtained in the same manner as in Example 3 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (2).

[0275] [Example 9]

[0276] As shown in Table 1, a reinforcing film (9) was obtained in the same manner as in Example 4 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (2).

[0277] [Example 10]

[0278] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (1) obtained in Example 1 to obtain a reinforcement film (10) with a surface protection film. The results are shown in Table 1.

[0279] [Example 11]

[0280] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (2) obtained in Example 2 to obtain a reinforcement film (11) with a surface protection film. The results are shown in Table 1.

[0281] [Example 12]

[0282] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (3) obtained in Example 3 to obtain a reinforcement film (12) with a surface protection film. The results are shown in Table 1.

[0283] [Example 13]

[0284] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (4) obtained in Example 4 to obtain a reinforcement film (13) with a surface protection film. The results are shown in Table 1.

[0285] [Example 14]

[0286] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (5) obtained in Example 5 to obtain a reinforcement film (14) with a surface protection film. The results are shown in Table 1.

[0287] [Example 15]

[0288] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (6) obtained in Example 6 to obtain a reinforcement film (15) with a surface protection film. The results are shown in Table 1.

[0289] [Example 16]

[0290] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (7) obtained in Example 7 to obtain a reinforcement film (16) with a surface protection film. The results are shown in Table 1.

[0291] [Example 17]

[0292] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (8) obtained in Example 8 to obtain a reinforcement film (17) with a surface protection film. The results are shown in Table 1.

[0293] [Example 18]

[0294] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (9) obtained in Example 9 to obtain a reinforcement film (18) with a surface protection film. The results are shown in Table 1.

[0295] [Example 19]

[0296] As shown in Table 1, a reinforcing film (19) was obtained in the same manner as in Example 1 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (7).

[0297] [Example 20]

[0298] As shown in Table 1, a reinforcing film (20) was obtained in the same manner as in Example 2 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (7).

[0299] [Example 21]

[0300] As shown in Table 1, a reinforcing film (21) was obtained in the same manner as in Example 3 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (7).

[0301] [Example 22]

[0302] As shown in Table 1, a reinforcing film (22) was obtained in the same manner as in Example 4 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (7).

[0303] [Example 23]

[0304] As shown in Table 1, a reinforcing film (23) was obtained in the same manner as in Example 5 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (7).

[0305] [Example 24]

[0306] As shown in Table 1, a reinforcing film (24) was obtained in the same manner as in Example 1 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (8).

[0307] [Example 25]

[0308] As shown in Table 1, a reinforcing film (25) was obtained in the same manner as in Example 2 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (8).

[0309] [Example 26]

[0310] As shown in Table 1, a reinforcing film (26) was obtained in the same manner as in Example 3 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (8).

[0311] [Example 27]

[0312] As shown in Table 1, a reinforcing film (27) was obtained in the same manner as in Example 4 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (8).

[0313] [Example 28]

[0314] As shown in Table 1, a reinforcing film (28) was obtained in the same manner as in Example 5 except that the (meth)acrylic adhesive composition (1) was changed to the (meth)acrylic adhesive composition (8).

[0315] [Example 29]

[0316] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (19) obtained in Example 19 to obtain a reinforcement film (29) with a surface protection film. The results are shown in Table 1.

[0317] [Example 30]

[0318] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (20) obtained in Example 20 to obtain a reinforcement film (30) with a surface protection film. The results are shown in Table 1.

[0319] [Example 31]

[0320] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (21) obtained in Example 21 to obtain a reinforcement film (31) with a surface protection film. The results are shown in Table 1.

[0321] [Example 32]

[0322] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (22) obtained in Example 22 to obtain a reinforcement film (32) with a surface protection film. The results are shown in Table 1.

[0323] [Example 33]

[0324] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (23) obtained in Example 23 to obtain a reinforcement film (33) with a surface protection film. The results are shown in Table 1.

[0325] [Example 34]

[0326] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (24) obtained in Example 24 to obtain a reinforcement film (34) with a surface protection film. The results are shown in Table 1.

[0327] [Example 35]

[0328] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (25) obtained in Example 25 to obtain a reinforcement film (35) with a surface protection film. The results are shown in Table 1.

[0329] [Example 36]

[0330] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (26) obtained in Example 26 to obtain a reinforcement film (36) with a surface protection film. The results are shown in Table 1.

[0331] [Example 37]

[0332] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (27) obtained in Example 27 to obtain a reinforcement film (37) with a surface protection film. The results are shown in Table 1.

[0333] [Example 38]

[0334] The surface protection film (C) obtained in Production Example 18 was bonded to the substrate of the reinforcement film (28) obtained in Example 28 to obtain a reinforcement film (38) with a surface protection film. The results are shown in Table 1.

[0335] [Table 1]

[0336]

[0337] [Comparative Example 1]

[0338] The (meth)acrylic adhesive composition (3) was applied to the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) of a polyester resin having a thickness of 25 μm and subjected to silicone treatment on one side in a manner of 25 μm after drying, and cured and dried under the conditions of a drying temperature of 130°C and a drying time of 3 minutes. In this way, an adhesive layer formed by the (meth)acrylic adhesive composition (3) was provided on the silicone-treated surface. Next, the surface of the TAC film substrate (A) having an anti-reflection layer on which the anti-reflection layer was not applied was bonded to the surface of the obtained adhesive layer to obtain a reinforcing film (C1). The obtained reinforcing film (C1) was aged at room temperature for 7 days. The results are shown in Table 2.

[0339] [Comparative Example 2]

[0340] As shown in Table 2, a reinforcing film (C2) was obtained in the same manner as in Comparative Example 1 except that the substrate was changed to a PET film substrate (B) having an antireflection layer.

[0341] [Comparative Example 3]

[0342] As shown in Table 2, a reinforcing film (C3) was obtained in the same manner as in Comparative Example 1 except that the substrate was changed to a TAC film (TG60UL, manufactured by FUJIFILM Corporation).

[0343] [Comparative Example 4]

[0344] As shown in Table 2, a reinforcing film (C4) was obtained in the same manner as in Comparative Example 1 except that the substrate was changed to a PET film (Lumirror U48, manufactured by Toray Industries, Inc.).

[0345] [Comparative Example 5]

[0346] As shown in Table 2, a reinforcing film (C5) was obtained in the same manner as in Comparative Example 1 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (4).

[0347] [Comparative Example 6]

[0348] As shown in Table 2, a reinforcing film (C6) was obtained in the same manner as in Comparative Example 2 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (4).

[0349] [Comparative Example 7]

[0350] As shown in Table 2, a reinforcing film (C7) was obtained in the same manner as in Comparative Example 3 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (4).

[0351] [Comparative Example 8]

[0352] As shown in Table 2, a reinforcing film (C8) was obtained in the same manner as in Comparative Example 4 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (4).

[0353] [Comparative Example 9]

[0354] As shown in Table 2, a reinforcing film (C9) was obtained in the same manner as in Comparative Example 1 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (5).

[0355] [Comparative Example 10]

[0356] As shown in Table 2, a reinforcing film (C10) was obtained in the same manner as in Comparative Example 2 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (5).

[0357] [Comparative Example 11]

[0358] As shown in Table 2, a reinforcing film (C11) was obtained in the same manner as in Comparative Example 3 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (5).

[0359] [Comparative Example 12]

[0360] As shown in Table 2, a reinforcing film (C12) was obtained in the same manner as in Comparative Example 4 except that the (meth)acrylic adhesive composition (3) was changed to the (meth)acrylic adhesive composition (5).

[0361] [Comparative Example 13]

[0362] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C1) obtained in Comparative Example 1 to obtain a reinforcement film (C13) with a surface protection film.

[0363] [Comparative Example 14]

[0364] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C2) obtained in Comparative Example 2 to obtain a reinforcement film (C14) with a surface protection film.

[0365] [Comparative Example 15]

[0366] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C3) obtained in Comparative Example 3 to obtain a reinforcement film with a surface protection film (C15).

[0367] [Comparative Example 16]

[0368] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C4) obtained in Comparative Example 4 to obtain a reinforcement film (C16) with a surface protection film.

[0369] [Comparative Example 17]

[0370] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C5) obtained in Comparative Example 5 to obtain a reinforcement film with a surface protection film (C17).

[0371] [Comparative Example 18]

[0372] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C6) obtained in Comparative Example 6 to obtain a reinforcement film (C18) with a surface protection film.

[0373] [Comparative Example 19]

[0374] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C7) obtained in Comparative Example 7 to obtain a reinforcement film (C19) with a surface protection film.

[0375] [Comparative Example 20]

[0376] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C8) obtained in Comparative Example 8 to obtain a reinforcement film (C20) with a surface protection film.

[0377] [Comparative Example 21]

[0378] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C9) obtained in Comparative Example 9 to obtain a reinforcement film (C21) with a surface protection film.

[0379] [Comparative Example 22]

[0380] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C10) obtained in Comparative Example 10 to obtain a reinforcement film (C22) with a surface protection film.

[0381] [Comparative Example 23]

[0382] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C11) obtained in Comparative Example 11 to obtain a reinforcement film (C23) with a surface protection film.

[0383] [Comparative Example 24]

[0384] The surface protection film (C) obtained in Production Example 15 was bonded to the substrate of the reinforcement film (C12) obtained in Comparative Example 12 to obtain a reinforcement film (C24) with a surface protection film.

[0385] [Table 2]

[0386]

[0387] Industrial Applicability

[0388] The reinforcing film and the reinforcing film with a surface protection film of the present invention can be used typically in the fields of optical components and electronic components.

[0389] Description of Reference Numerals

[0390] 1000 Reinforcement film with surface protection film

[0391] 100 Reinforcement film

[0392] 200 Surface protection film

[0393] 10 Base material layer A1

[0394] 20 Adhesive layer A2

[0395] 30 Functional layer A3

[0396] 40 base material layer B1

[0397] 50 Adhesive layer B2

[0398] 60 Peel Sheet

[0399] 70 Functional layer B3

Claims

1. A reinforcing film comprising, in order, a functional layer A3, a substrate layer A1 and an adhesive layer A2, The functional layer A3 is an anti-reflection layer. The substrate layer A1 is a resin sheet composed of triacetyl cellulose or polyimide. The adhesive layer A2 is formed from an adhesive composition a2. The adhesive composition a2 comprises an acrylic polymer and at least one selected from the group consisting of a multifunctional isocyanate crosslinking agent and an epoxy crosslinking agent. The total light transmittance of the substrate layer A1 is above 90%. After the reinforcing film was stored in an environment of 60° C. and 90% RH for one week, the change rate of light reflectance at 580 nm was 2.0% or less.

2. The reinforcing film according to claim 1, wherein: The haze change rate of the reinforcing film after being stored in an environment of 60° C. and 90% RH for one week is 10.0% or less.

3. The reinforcing film according to claim 1, wherein: The adhesive layer A2 was affixed to a PET film and left at 23° C. for 30 minutes, and the adhesive strength to the PET film at a peeling angle of 180 degrees and a peeling speed of 300 mm / min was 0.30 N / 25 mm or more. 4 . The reinforcing film according to claim 1 , which is attached to an adherend, and the adherend is an optical component or an electronic component. 5 . An optical component with a reinforcing film or an electronic component with a reinforcing film, comprising the reinforcing film according to claim 1 . 6 . A reinforcing film with a surface protection film, comprising a surface protection film on the surface of the functional layer A3 of the reinforcing film according to claim 1 .

7. The reinforcing film with a surface protection film according to claim 6, wherein: The reinforcing film with a surface protection film was stored in an environment of 60° C. and 90% RH for 1 week, and then after the surface protection film was peeled off, the change rate of light reflectance of the reinforcing film at 580 nm was 5.0% or less.

8. A method for using a reinforcing film with a surface protection film, wherein: The adhesive layer A2 of the reinforcing film with a surface protection film according to claim 6 is exposed and the adhesive layer A2 is attached to an adherend, and then the surface protection film is peeled off.

Citation Information

Patent Citations

  • JP1988066199A

  • Acrylic adhesives and its production method

    JP2002069411A

  • Surface protective film

    JP2016017109A

  • Surface protective film and optical member with protective film

    JP2019127526A

  • Antireflection film, display device using antireflection film, and selection method of antireflection film

    JP2019144577A